2021
DOI: 10.1099/ijsem.0.004608
|View full text |Cite
|
Sign up to set email alerts
|

Parvularcula mediterranea sp. nov., isolated from marine plastic debris from Zakynthos Island, Greece

Abstract: A Gram-negative, dark orange-pigmented, aerobic, non-spore-forming, coccoid-shaped bacterium designated as ZS-1/3T was isolated from a floating plastic litter (polypropylene straw) sample, collected from shallow seawater near the public beach of Laganas on Zakynthos island, Greece. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the isolate is affiliated with the genus Parvularcula in the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Major characteristics that distinguished strain BGMRC 0090 T from the closest recognized species Strains: 1, BGMRC 0090 T (this study); 2, Parvularcula lutaonensis CC-MMS-1 T (this study); 3, Parvularcula mediterranea ZS-1/3 T , data from Al-Omari et al[6]; 4, Parvularcula dongshanensis SH25 T , data from Yu et al[7]; 5, Parvularcula marina SM1705 T , data from Sun et al[5]; 6, Parvularcula bermudensis HTCC2503 T , data from Cho et al[3]. All strains were Gram-negative, positive for catalase, alkaline phosphatase, esterase (C4), esterase lipase (C8), a-chymotrypsin and β-galactosidase (PNPG), gelatin hydrolysis and utilization; but negative for oxidase, lipase (C14), lipase (C14), Nacetyl-β-glucosaminidase, α-fucosidase, indole production, acid production from glucose, arginine dihydrolase, and assimilation of l-arabinose, Nacetylglucosamine, capric acid, malic acid and phenylacetic acid.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Major characteristics that distinguished strain BGMRC 0090 T from the closest recognized species Strains: 1, BGMRC 0090 T (this study); 2, Parvularcula lutaonensis CC-MMS-1 T (this study); 3, Parvularcula mediterranea ZS-1/3 T , data from Al-Omari et al[6]; 4, Parvularcula dongshanensis SH25 T , data from Yu et al[7]; 5, Parvularcula marina SM1705 T , data from Sun et al[5]; 6, Parvularcula bermudensis HTCC2503 T , data from Cho et al[3]. All strains were Gram-negative, positive for catalase, alkaline phosphatase, esterase (C4), esterase lipase (C8), a-chymotrypsin and β-galactosidase (PNPG), gelatin hydrolysis and utilization; but negative for oxidase, lipase (C14), lipase (C14), Nacetyl-β-glucosaminidase, α-fucosidase, indole production, acid production from glucose, arginine dihydrolase, and assimilation of l-arabinose, Nacetylglucosamine, capric acid, malic acid and phenylacetic acid.…”
mentioning
confidence: 67%
“…The ANIb, ANIm, AAI and dDDH values between strain BGMRC 0090 T and five closely Parvularcula species were 67.5–73.0 %, 83.7–84.0 %, 55.5–69.2 % and 18.9–21.4 % (Table S2), respectively. The ANI, AAI and dDDH values were much lower than the threshold values of ANI (95~96 %), AAI (95.0~95.5 %) and DDH (70 %) to discriminate bacterial species [6]. In addition, the phylogenomic trees based on 87 housekeeping genes showed that strain BGMRC 0090 T formed an independent branch with P.…”
Section: Overall Genomic Relatedness Indices and Phylogenomicsmentioning
confidence: 99%
See 3 more Smart Citations